The Oldest Vita Icons of Saint Nicolas the Wonderworker in Byzantine and Old Russian Art: The Boundaries of Byzantine and Latin in Iconography and Art Style - Makhanko, Maria A. (Actual Problems of Theory and History of Art, 2019)
Degree of veneration of St. Nicholas, Archbishop of Myra in Lycia (ancient Asia Minor), was extremely high already in the Middle Byzantine period (10th–12th centuries). The most ancient Byzantine examples were preserved on the borders of the former empire or in the zones of its cultural influence and contact with other cultures, primarily the Latin one — in Sinai, Cyprus, and Great Greece (southern Italy).The comparison of the oldest Russian vita icon of Saint Nicolas Wonderworker (from the villages of Luboni and Ozerevo at the land of Novgorod the Great, now in the State Russian Museum of St. Petersburg) with the earliest known icons of the Saint, from the collection of the Sinai Monastery, from Apulia (now in Pinacothecain Bari) and from the church of St. Nicholas tes Steges near the village of Kakopetria on Cyprus (the last both from the middle or second half of the 13th century) shows a mixture of Byzantine and Latin features in the iconography and art style of Russian monuments: the different size of the scenes, the central figures,the design of compositions, the drawings and painting of the faces, the painting method, the use of more orless decorative elements. Such a synthetic “atmosphere” indicates an active cultural exchange, the unfinished processes of forming of vita icons as an iconographic type.